Usefulness Of Surrogate Markers Of Body Fat Distribution For Predicting Metabolic Syndrome In Middle-Aged And Older Korean Populations - Shin KA (Dove Medical Press, 2019)
Kyung-A Shin,1 Young-Joo Kim2 1Department of Clinical Laboratory Science, Shinsung University, Chungnam, Republic of Korea; 2Department of Exercise Rehabilitation Welfare Soojung Campus, Sungshin University, Seoul, Republic of KoreaCorrespondence: Young-Joo KimDepartment of Exercise Rehabilitation Welfare Soojung Campus, Sungshin University, 2, Bomun-ro 34da-gil, Seoungbuk-gu, Seoul 02844, South KoreaTel/Fax + 822-920-7942Email kyj87@sungshin.ac.krBackground: Obesity markers, the lipid accumulation product (LAP), visceral adiposity index (VAI), triglyceride and glucose (TyG) index, and waist-to-height ratio (WHtR) are useful for assessing the risk of obesity-related cardiovascular disease. However, no previous study has assessed the usefulness of these four indices as predictors of metabolic syndrome among middle-aged and older Korean populations.Purpose: To investigate the usefulness of LAP, VAI, TyG index, and WHtR as predictors of metabolic syndrome in middle-aged and older Korean populations.Methods: This study included 15,490 male and female adults aged 40 years or older who underwent a medical check-up in a general hospital located in a Korean metropolitan area between January 2015 and December 2016. The diagnostic criteria for metabolic syndrome suggested by the American Heart Association/National Heart Lung and Blood Institute were used. LAP, VAI, and TyG index were computed based on the suggested mathematical models. WHtR was computed by dividing waist circumference by height. The independent sample t-test, one-way analysis of variance, Scheffe test, chi-square test, Pearson’s correlation analysis, and logistic regression were used to analyze the data.Results: LAP, VAI, TyG index, and WHtR were significantly related to metabolic syndrome in both sexes. Receiver operating characteristic curve analysis showed the following optimal cutoffs for LAP, VAI, TyG index, and WHtR: 33.97, 1.84, 8.81, and 0.51, respectively. After adjusting for latent confounding variables (age, systolic blood pressure, diastolic blood pressure, and waist circumference), LAP, VAI, TyG index, and WHtR were significantly correlated with metabolic syndrome. Area under the curve (AUC) values based on ROC curves showed that LAP, VAI, TyG index, and WHtR were reliable predictors of metabolic syndrome. LAP had the greatest AUC, suggesting that it was a more useful predictor than the other markers (AUC=0.917, 95% confidence interval: 0.913–0.922).Conclusion: LAP, VAI, TyG index, and WHtR are useful predictors of metabolic syndrome in middle-aged and older Koreans, but LAP had the greatest diagnostic accuracy.Keywords: metabolic syndrome, LAP, VAI, TyG index, WHtR